2020
DOI: 10.14445/22315381/cati1p217
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Learning Management Systems with PLE – a Review Paper

Abstract: Electronic Learning (E-Learning) evolves consistently. An effective eLearning has unrelenting readiness in integrating new paradigms while the students become the core of the process. In this regard, the current tools are replaced by others, with customization under consideration. Somehow, changes are costly and should not be merely focusing on replacing all past initiatives but also should attempt to combine the new initiatives with the successful ones, in order that the great robustness and effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…One of the applications of knowledge management explains the usage of knowledge sharing scheme for business intelligence in varying transformations of tactic knowledge and explicit knowledge in e-business system. Innovatively four matrices and four indices were applied in the e-business, this supports the online stores to examine the data with web usage analysis [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the applications of knowledge management explains the usage of knowledge sharing scheme for business intelligence in varying transformations of tactic knowledge and explicit knowledge in e-business system. Innovatively four matrices and four indices were applied in the e-business, this supports the online stores to examine the data with web usage analysis [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…20 Hamzah et al, found that government bureaucracies have created barriers to government services and caused poor accountability and transparency, thus, discouraging citizens' dealings with government agencies. 21 Therefore, society must change and be open to technology. The e-government must quickly implemented so that the citizens and government can make a connection to the virtual space that created and strengthened through the leadership that support governance framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The e-government must quickly implemented so that the citizens and government can make a connection to the virtual space that created and strengthened through the leadership that support governance framework. 21 The government acknowledges that technology enables various social problems, including corruption, to be addressed and will continue to find the best mechanisms by using the latest technologies to combat corruption. As stated by Ramli, a positive connection between corruption and e-government when society reaches high level of economic growth and development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hamzah et al ., found that government bureaucracies have created barriers to government services and caused poor accountability and transparency, thus, discouraging citizens’ dealings with government agencies. 23 Therefore, society must change and be open to technology. The e-government must quickly implemented so that the citizens and government can make a connection to the virtual space that created and strengthened through the leadership that support governance framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The e-government must quickly implemented so that the citizens and government can make a connection to the virtual space that created and strengthened through the leadership that support governance framework. 23 The government acknowledges that technology enables various social problems, including corruption, to be addressed and will continue to find the best mechanisms by using the latest technologies to combat corruption. As stated by Ramli, a positive connection between corruption and e-government when society reaches high level of economic growth and development.…”
Section: Literature Reviewmentioning
confidence: 99%